Desarrollo de una herramienta web para la corrección gramatical de la escritura en idioma inglés mediante técnicas de procesamiento de lenguaje natural - Hidalgo Carrera, Cristhian Alexander (2024)
In a globalized world where proficiency in English is crucial, the disparity in writing skills, particularly among non-native speakers, motivated the development of "MindTer," an innovative tool powered by artificial intelligence and focused on natural language processing techniques. This project was proposed as a solution for correcting grammatical errors in English and improving written communicative competencies, facilitating self-directed learning and supporting educators in English teaching, thereby promoting linguistic fluency in a digital and global environment. A systematic mapping approach was employed to identify implementable NLP models for the tool, and its construction followed the prototyping methodology. User testing was conducted remotely, utilizing usability techniques and the SUS questionnaire, accommodating the geographical dispersion of participants. The usability evaluation results yielded an average SUS score of 77.0, indicating a favorable perception of the tool. These results, along with identified areas for improvement, lay a solid foundation for future updates, thus contributing to excellence in English teaching and grammatical correction. This work highlights the significance of integrating advanced technologies in language learning and suggests a promising path towards the personalization and enhancement of linguistic education.